Debt and earnings management in Indonesia: An issue of free cash-flow or covenant? - Muhammad Agung Prabowo; Jaka Winarna; Y. Anni Aryani; Falikhatun Falikhatun; Evi Gantyowati (Jurnal Keuangan dan Perbankan, 2020)
This paper investigates the effect of corporate debt on the pattern of earnings management in Indonesia. The issues motivating the paper stems from research gap that has been left unattended. Specifically previous works has been found as failing to differentiate between trade payable and private debt and omitting the variation of liquidity, of which has been claimed as provide conditional effect to the magnitude of corporate debt. The conceptual framework borrows agency theory and follow the arguments of free-cash flow perspective as well as covenant hypothesis. Analysis is based on a sample set consisting of 497 firms engaging in manufacturing operations listed in Indonesia Stock Exchange during the period of 2009 to 2014. The results reveal that corporate debt is an important determinant of earnings management statistically and economically. The results are robust after controlling for debt specifications. Further tests reveal that the interaction between liquidity and specification of corporate debt shapes different pattern of the directions of earnings management. Yet, a due care is required in interpreting the results as this research might suffer from several shortcomings.JEL Classifications: G32, G34, M41 How to Cite:Prabowo, M. A., Winarna, J., Aryani, Y. A., Falikhatun, Gantyowati, E.(2020). The level of debt and earnings management in Indonesia: An issue offree cash-flow or covenant? Jurnal Keuangan dan Perbankan, 24(2), 142-55.DOI: https://doi.org/10.26905/jkdp.v24i2.4043